Manufacturing method of extruded thermoplastic resin foam board

The method addresses the stability and thermal conductivity issues of conventional extruded foam plates by using styrene-(meth)acrylic acid ester copolymer as the base resin and HFO as the physical blowing agent, resulting in improved moldability and long-term heat insulation.

JP7671230B2Active Publication Date: 2025-05-01JSP CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021178779
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-01
Publication Date
2025-05-01
Estimated Expiration
2041-11-01

AI Technical Summary

Technical Problem

Conventional extruded foam plates made from polystyrene resin with hydrofluoroolefin (HFO) as the physical foaming agent suffer from reduced foamability and stability, leading to increased thermal conductivity over time due to air infiltration and HFO dissipation.

Method used

A method for manufacturing thermoplastic resin extruded foam plates using a base resin primarily composed of styrene-(meth)acrylic acid ester copolymer, combined with HFO as the physical blowing agent, and a flame retardant, to achieve improved formability, stability, and low long-term thermal conductivity.

Benefits of technology

The method enables the stable production of extruded foam plates with excellent moldability and long-term heat insulation properties, maintaining low thermal conductivity even after extended periods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671230000001
    Figure 0007671230000001
  • Figure 0007671230000002
    Figure 0007671230000002
  • Figure 0007671230000003
    Figure 0007671230000003
Patent Text Reader

Abstract

To provide a method for manufacturing a thermoplastic resin extrusion foam plate which enables stable manufacture of a thermoplastic resin extrusion foam plate having low long-term heat conductivity, and is also excellent in moldability.SOLUTION: A method for manufacturing an extrusion foam plate extrudes and foams a foamable resin composition obtained by kneading a base material resin, a physical foaming agent and a flame retardant, and forms the foamable resin composition in a plate shape by a molding tool, wherein the base material resin contains a styrene-(meth)acrylate copolymer as a main component, a percentage content of the (meth)acrylate component in the base material resin is 25 mass% or more and 90 mass% or less, the total blending amount of the physical foaming agent is within a specific range, the physical foaming agent contains hydrofluoroolefin, and the total blending amount of the hydrofluoroolefin is within a specific range.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an extruded thermoplastic resin foam plate, and more particularly to a method for producing an extruded thermoplastic resin foam plate which has excellent moldability and production stability in extrusion foam molding and low long-term thermal conductivity. [Background technology]

[0002] Conventionally, a method has been known in which a cell control agent is added to a polystyrene resin, the mixture is heated and kneaded in an extruder, a physical foaming agent is then injected into the extruder and further kneaded, the resulting molten mixture is extruded from a high-pressure region to a low-pressure region (usually into the atmosphere), and the mixture is shaped into a plate by a shaping device connected to the die outlet of the extruder to obtain a thick extruded polystyrene resin foam plate.

[0003] The extruded foam board obtained by this method has low thermal conductivity and excellent heat insulating properties, and is therefore suitable for use as a heat insulating material for the walls, floors, roofs, etc. of buildings. However, conventional extruded foam boards used polystyrene resin as the main component of the base resin and a mixture of isobutane and hydrofluoroolefin (hereinafter also referred to as HFO) as the physical foaming agent, so there was still room for improvement in terms of reducing thermal conductivity and improving insulation.

[0004] That is, the thermal conductivity of the extruded foam board is influenced by the thermal conductivity of the thermoplastic resin and the thermal conductivity of the residual physical foaming agent, and is particularly strongly influenced by the thermal conductivity of the residual physical foaming agent. Therefore, if the thermal conductivity of the physical foaming agent itself is small, the extruded foam board can have a low thermal conductivity immediately after production. However, if the permeability coefficient of the physical foaming agent through the bubble membrane is large, the amount of the physical foaming agent remaining in the bubble decreases over time, and at the same time, air with high thermal conductivity penetrates into the bubble, so that the thermal conductivity of the extruded foam board tends to be high.

[0005] From this point of view, the above-mentioned isobutane has a lower thermal conductivity than air, but has a large permeability coefficient for the polystyrene-based resin bubble membrane, so there is room for improvement in terms of maintaining a low thermal conductivity over a long period of time. In order to obtain an extruded foam board with excellent long-term thermal conductivity (long-term thermal conductivity), it is preferable to use a physical foaming agent that has a lower thermal conductivity than air, a small gas permeability coefficient, and can maintain a low thermal conductivity over a long period of time. An example of a physical foaming agent that meets this requirement is hydrofluoroolefin (HFO).

[0006] However, in the conventional technology, when a polystyrene resin is used as the base resin and a hydrofluoroolefin is used as the physical foaming agent, the foamability of the molten mixture containing the polystyrene resin and the physical foaming agent decreases. Therefore, it has been desired to more stably produce a good extruded foam board.

[0007] On the other hand, attempts have been made to use a mixed resin of polystyrene resin and styrene-(meth)acrylic acid ester copolymer in the manufacture of extruded foam boards (for example, Patent Document 1). Furthermore, it is known that the permeability coefficient of the physical foaming agent for the styrene-(meth)acrylic acid ester copolymer is much smaller than that for the polystyrene resin. Therefore, it is expected that an extruded foam board with low thermal conductivity can be obtained for a long period of time by using a styrene-(meth)acrylic acid ester copolymer instead of a polystyrene resin, or by using a polystyrene resin and a styrene-(meth)acrylic acid ester copolymer in combination. In addition, since the permeability coefficient of the styrene-(meth)acrylic acid ester copolymer for air is smaller than that of the polystyrene resin, it is also expected to suppress the increase in thermal conductivity caused by air penetrating into the bubbles of the extruded foam board. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2008-133424 A Summary of the Invention [Problem to be solved by the invention]

[0009] However, in the past, there have been no attempts to use a styrene-(meth)acrylic acid ester copolymer as the main component of a base resin and combine it with a hydrofluoroolefin (HFO). For example, in Patent Document 1, although a base resin consisting of a polystyrene resin and a styrene-(meth)acrylic acid ester copolymer is used, the physical blowing agent disclosed is only a mixed blowing agent of isobutane and methyl chloride.

[0010] Furthermore, in the prior art, resins mainly composed of styrene-(meth)acrylic acid ester copolymers have poor foaming properties when a physical foaming agent such as butane is used, so there is still room for improvement in terms of stably producing extruded foam boards with large cross-sectional areas.

[0011] The present invention aims to provide a method for producing an extruded thermoplastic resin foam board that can stably produce an extruded thermoplastic resin foam board with low long-term thermal conductivity, and that has excellent moldability during extrusion foaming (hereinafter simply referred to as moldability) to easily obtain a board-shaped foam. [Means for solving the problem]

[0012] According to the present invention, there is provided a method for producing an extruded thermoplastic resin foam plate as described below. [1] A method for producing an extruded thermoplastic resin foam plate, comprising the steps of extruding and foaming a foamable resin composition obtained by kneading a base resin, a physical foaming agent, and a flame retardant, and molding the composition into a plate shape using a molding tool, The base resin is mainly composed of a styrene-(meth)acrylic acid ester copolymer, the content of a (meth)acrylic acid ester component derived from a styrene-(meth)acrylic acid ester copolymer in the base resin is 25% by mass or more and 90% by mass or less; the total amount of the physical foaming agents is 0.8 mol or more and 1.3 mol or less per kg of the base resin; A method for producing an extruded thermoplastic resin foam board, wherein the physical foaming agent contains a hydrofluoroolefin, and the total amount of the hydrofluoroolefin blended is 0.5 mol or more and 1.3 mol or less per kg of the base resin. [2] The method for producing an extruded thermoplastic resin foam board according to item 1, wherein the content of the (meth)acrylic acid ester component derived from the styrene-(meth)acrylic acid ester copolymer in the base resin is 50% by mass or more and 80% by mass or less. [3] The method for producing a thermoplastic resin foam board according to the above item 1 or 2, wherein the styrene-(meth)acrylic acid ester copolymer is a styrene-methyl methacrylate copolymer. [4] The method for producing a thermoplastic resin foam board according to any one of [1] to [3], wherein the total amount of the hydrofluoroolefins is 0.5 mol or more and 1.0 mol or less per 1 kg of the base resin. [5] The hydrofluoroolefin comprises 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) and / or 1,3,3,3-tetrafluoropropene (HFO-1234ze); 5. The method for producing a thermoplastic resin foam board according to any one of the above items 1 to 4, characterized in that the total amount of 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) and / or 1,3,3,3-tetrafluoropropene (HFO-1234ze) is 0.5 mol or more per kg of the base resin. [6] The method for producing a thermoplastic resin foam board according to any one of the above items 1 to 4, wherein the hydrofluoroolefin contains 1,3,3,3-tetrafluoropropene (HFO-1234ze), and the amount of the 1,3,3,3-tetrafluoropropene (HFO-1234ze) blended is 0.5 mol or more per kg of the base resin. [7] The method for producing a thermoplastic resin foam board according to item 6 above, wherein the content (X) [mass %] of a (meth)acrylic acid ester component derived from a styrene-(meth)acrylic acid ester copolymer in the base resin and the amount (Y) [mol / kg of base resin] of 1,3,3,3-tetrafluoropropene (HFO-1234ze) satisfy the following formula (1): Y < 0.024X-0.4 (1) Effect of the Invention

[0013] The present invention enables the easy and stable production of extruded thermoplastic resin foam boards which have excellent moldability and can be easily shaped into plate shapes, and the extruded foam boards obtained have low long-term thermal conductivity and can maintain excellent heat insulation properties for a long period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In the method for producing an extruded thermoplastic resin foam board of the present invention, a thermoplastic resin extruded foam board (hereinafter also referred to as an extruded foam board) is produced by a method including a step of extruding and foaming a foamable resin composition obtained by kneading a base resin, a physical foaming agent, and a flame retardant, and molding the composition into a plate shape using a molding tool. Specifically, for example, a base resin is added with a flame retardant and additives such as a cell regulator, and the mixture is fed to an extruder, heated and kneaded, and then a physical foaming agent is pressed into the extruder and further kneaded to obtain a foamable resin composition, which is extruded from a high pressure region to a low pressure region (usually into the atmosphere) to be foamed, and the resulting foam is shaped into a plate shape using a shaping device (such as a guider) connected to the die outlet of the extruder, thereby producing an extruded thermoplastic resin foam board. As the shaping device, for example, a device consisting of a pair of upper and lower polytetrafluoroethylene plates is used.

[0015] In the present invention, the base resin is mainly composed of a styrene-(meth)acrylic acid ester copolymer, which has a smaller permeability coefficient for hydrofluoroolefins (HFOs) and also has a smaller permeability coefficient for air than the polystyrene resins conventionally used in the manufacture of extruded foam boards, and is therefore a preferred resin in that it can be used to obtain an extruded foam board with excellent long-term thermal insulation properties.

[0016] The styrene-(meth)acrylic acid ester copolymer is a copolymer of styrene and a lower alkyl ester of (meth)acrylic acid, and specifically includes, for example, a styrene-methyl acrylate copolymer, a styrene-ethyl acrylate copolymer, a styrene-propyl acrylate copolymer, a styrene-methyl methacrylate copolymer, a styrene-ethyl methacrylate copolymer, and a styrene-propyl methacrylate copolymer. Among these copolymers, a styrene-methyl acrylate copolymer and a styrene-methyl methacrylate copolymer are preferred, and a styrene-methyl methacrylate copolymer is more preferred. These styrene-(meth)acrylic acid ester copolymers can be used alone or in combination of two or more. In this specification, "(meth)acrylic acid" is a concept that includes "acrylic acid" and "methacrylic acid", and means one or both of them.

[0017] In this specification, the base resin mainly composed of a styrene-(meth)acrylic acid ester copolymer means that the content of the styrene-(meth)acrylic acid ester copolymer in the base resin is 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more, including 100% by mass. The higher the content, the smaller the gas permeability coefficient of the physical foaming agent and air through the base resin, which is preferable.

[0018] Furthermore, in the base resin, the content of the (meth)acrylic acid ester component derived from the styrene-(meth)acrylic acid ester copolymer is 25% by mass or more and 90% by mass or less. This configuration is closely related to the use of hydrofluoroolefin (HFO) described later as a physical foaming agent, and the present invention is characterized in that the base resin containing the high content of the (meth)acrylic acid ester component is used in combination with HFO. That is, when the HFO is used as a physical foaming agent, even if the content of the (meth)acrylic acid ester component is high, it is possible to obtain a good extruded foam board with excellent foamability and moldability. From this viewpoint, the content is preferably 30% by mass or more and 85% by mass or less, more preferably 40% by mass or more and 80% by mass or less, and even more preferably 50% by mass or more and 80% by mass or less.

[0019] In the present invention, two or more types of styrene-(meth)acrylic acid ester copolymers having different contents of (meth)acrylic acid ester components can be used in combination. In this case, the total of the contents of the (meth)acrylic acid ester components contained in each styrene-(meth)acrylic acid ester copolymer is defined as the content of the (meth)acrylic acid ester component of the styrene-(meth)acrylic acid ester copolymer.

[0020] If the content of the (meth)acrylic acid ester component in the base resin is too low, the effect of maintaining low thermal conductivity (preventing deterioration of thermal insulation property) that prevents the thermal conductivity of the extruded foam board from increasing by preventing the dissipation of hydrofluoroolefin described later will be small. In addition, HFO will be easily separated from the foam board, and gas spots will occur frequently, which may cause the appearance of the surface of the extruded foam board to deteriorate. On the other hand, if the content of the (meth)acrylic acid ester component is too high, the effect of maintaining low thermal conductivity will be obtained, but the moldability will decrease and it may become impossible to obtain an extruded foam board. In addition, the flame retardancy may deteriorate, and it may not be possible to satisfy the flame retardancy standard required for building materials. However, the flame retardancy is also affected by the type and amount of flame retardant used in production, the density of the extruded foam, and the type and remaining amount of the blowing agent in the extruded foam.

[0021] The effect of maintaining low thermal conductivity by the styrene-(meth)acrylic acid ester copolymer is realized by the combined effect of the (meth)acrylic acid ester component in suppressing the escape of HFO, which has low thermal conductivity, from the extruded foam plate and the inflow of air, which has high thermal conductivity, into the extruded foam plate. Therefore, when the (meth)acrylic acid ester component in the styrene-(meth)acrylic acid ester copolymer is reduced, the HFO is more likely to escape from the extruded foam plate, and the thermal conductivity of the extruded foam plate is more likely to increase. However, when an extruded foam is produced using only a styrene-(meth)acrylic acid ester copolymer with an excessively high (meth)acrylic acid ester component, as described above, the moldability is reduced and it becomes difficult to satisfy the flame retardant standard.

[0022] Therefore, when using a styrene-(meth)acrylic acid ester copolymer with a high (meth)acrylic acid ester content, it is preferable to use a styrene-(meth)acrylic acid ester copolymer with a low (meth)acrylic acid ester content in combination, so that the content of the (meth)acrylic acid ester component falls within the range described above.

[0023] When a styrene-(meth)acrylic acid ester copolymer having a large amount of (meth)acrylic acid ester components is used in combination with a styrene-(meth)acrylic acid ester copolymer having a small amount of (meth)acrylic acid ester components, the styrene-(meth)acrylic acid ester copolymer having a large amount of the components preferably contains the components in an amount of 50% by mass or more and 85% by mass or less, more preferably contains the components in an amount of 60% by mass or more and 80% by mass or less.The styrene-(meth)acrylic acid ester copolymer having a small amount of the components preferably contains the components in an amount of 10% by mass or more and less than 50% by mass, more preferably contains the components in an amount of 15% by mass or more and 30% by mass or less.

[0024] The content of the (meth)acrylic acid ester component in the styrene-(meth)acrylic acid ester copolymer can be determined by a known method such as pyrolysis gas chromatography analysis.

[0025] In the present invention, other polymers such as polystyrene resin, polyester resin, polyolefin resin, styrene-based elastomer, and polyphenylene ether resin can be mixed into the base resin according to the purpose of blending, within the scope that does not impair the object of the present invention. The amount of such other polymers used in the base resin (based on the total base resin being 100% by mass) is preferably 30% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less. The polystyrene resin referred to here is one that does not contain a (meth)acrylic acid ester component in the polystyrene resin.

[0026] The physical blowing agent used in the method of the present invention contains hydrofluoroolefin (HFO). The HFO has zero or very low ozone depletion potential, low global warming potential, and is non-flammable. Furthermore, the HFO has low thermal conductivity in a gaseous state, so it can reduce the thermal conductivity of the extruded insulation foam.

[0027] The physical blowing agent used in the method of the present invention may be used in combination with a hydrocarbon having 1 to 5 carbon atoms such as isobutane, an aliphatic alcohol having 1 to 5 carbon atoms such as ethyl alcohol, water, a dialkyl ether having an alkyl chain with 1 to 3 carbon atoms, carbon dioxide, etc., within a range that does not impair long-term heat insulation properties.

[0028] The total amount of the physical foaming agents is 0.8 mol or more and 1.3 mol or less per kg of the base resin. If the total amount is within this range, an extruded foam board with a desired apparent density can be obtained. If the total amount is too small, an extruded foam board with a desired apparent density cannot be obtained. If the total amount is too large, the foaming agent is likely to separate from the foam board, and gas spots may occur frequently. For this reason, the total amount is preferably 0.9 mol or more and 1.2 mol or less.

[0029] The total amount of the HFO is 0.5 mol or more and 1.3 mol or less per kg of the base resin. If the total amount is too small, it may be impossible to obtain an extruded foam board having a low thermal conductivity over a long period of time. For this reason, the total amount is preferably 0.7 mol or more, more preferably 0.8 mol or more, and even more preferably 0.9 mol or more. If the total amount is too large, the HFO may easily separate from the foam board, which may cause frequent gas spots or reduced production stability. For this reason, the total amount is preferably 1.2 mol or less, more preferably 1.1 mol or less, and even more preferably 1 mol or less.

[0030] Specific examples of the HFO include 1-chloro-3,3,3-trifluoropropene (hereinafter also referred to as HFO-1233zd), 1,3,3,3-tetrafluoropropene (hereinafter also referred to as HFO-1234ze), 1-chloro-2,3,3,3-tetrafluoropropene (hereinafter also referred to as HFO-1224yd), 2,3,3,3-tetrafluoropropene (HFO-1234yf), 1,1,1,4,4,4-hexafluoro-2-butene (HFO-1336mzz), etc. These blowing agents can be used alone or in combination of two or more kinds.

[0031] Among these hydrofluoroolefins (HFOs), it is preferable to include 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) and / or 1,3,3,3-tetrafluoropropene (HFO-1234ze) as the physical blowing agent, since they have excellent heat insulating properties due to their small thermal conductivity and further have a small permeability coefficient and excellent long-term heat insulating properties.

[0032] Furthermore, 1,3,3,3-tetrafluoropropene (HFO-1234ze) has a smaller permeability coefficient for styrene-(meth)acrylic acid ester copolymers than 1-chloro-3,3,3-trifluoropropene (HFO-1233zd), so the thermal conductivity of the extruded foam board can be kept low for a long period of time. On the other hand, 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) has better foaming and moldability than 1,3,3,3-tetrafluoropropene (HFO-1234ze), so extruded foam boards can be produced stably, and its smaller thermal conductivity means that the thermal conductivity of the extruded foam board immediately after production can be reduced.

[0033] The total amount of 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) and / or 1,3,3,3-tetrafluoropropene (HFO-1234ze) is preferably 0.5 mol or more per kg of the base resin. If the total amount is within the above range, the amount of blowing agent remaining in the extruded foam plate after extrusion foaming is increased, resulting in an extruded foam plate with better long-term heat insulation. From this viewpoint, the total amount of 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) and / or 1,3,3,3-tetrafluoropropene (HFO-1234ze) is more preferably 0.7 mol or more, and even more preferably 0.8 mol or more per kg of the base resin. On the other hand, from the viewpoints of production stability and moldability, the upper limit of the total amount of 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) and / or 1,3,3,3-tetrafluoropropene (HFO-1234ze) is preferably 1.3 mol, more preferably 1.2 mol, still more preferably 1.1 mol, and particularly preferably 1 mol, per 1 kg of the base resin.

[0034] Furthermore, when HFO-1234ze and HFO-1233zd are used as the HFOs, from the viewpoint of excellent production stability, the molar ratio of HFO1234ze to HFO-1233zd (HFO-1234ze:HFO-1233zd) is preferably 30:70 to 90:10, more preferably 40:60 to 80:20, and even more preferably 50:50 to 70:30.

[0035] As mentioned above, 1,3,3,3-tetrafluoropropene (HFO-1234ze) has a small gas permeability coefficient, so that the thermal conductivity of the extruded foam board can be kept low for a long period of time. Therefore, the hydrofluoroolefin (HFO) preferably contains 1,3,3,3-tetrafluoropropene (HFO-1234ze), and the amount of the HFO is preferably 0.5 mol or more, more preferably 0.7 mol or more, and even more preferably 0.8 mol or more per 1 kg of the base resin. When the amount of 1,3,3,3-tetrafluoropropene (HFO-1234ze) satisfies the above range, the extruded foam board has better long-term heat insulation. From the viewpoint of manufacturing stability and moldability, the upper limit of the amount is preferably 1.3 mol, more preferably 1.2 mol, even more preferably 1.1 mol, and particularly preferably 1 mol per 1 kg of the base resin.

[0036] Furthermore, it is preferable that the content (X) [mass %] of the (meth)acrylic acid ester component and the blending amount (Y) [mol / kg of base resin] of 1,3,3,3-tetrafluoropropene (HFO-1234ze) satisfy the following formula (2). When the blending amount (Y) of HFO-1234ze satisfies the range determined by the formula (2), separation of HFO-1234ze from the molten resin is suppressed, and an extruded foam plate having excellent moldability without occurrence of gas spots and a good appearance on the surface of the extruded foam plate is easily obtained. For these reasons, it is more preferable that the following formula (1) is satisfied. Y < 0.024X-0.2 (2) Y < 0.024X-0.4 (1)

[0037] As described above, the method of the present invention is characterized in that it combines the use of a base resin containing a specific range of (meth)acrylic acid ester component as a main component with the use of the hydrofluoroolefin (HFO) as a physical foaming agent as a main component.

[0038] Conventionally, polystyrene resin has been used as the base resin for extruded foam boards, and a mixture of the main component isobutane and HFO has been used as the physical foaming agent. HFO is used because it is non-flammable, and it has a low thermal conductivity among physical foaming agents. However, HFO has low solubility in polystyrene resin and poor foaming ability among physical foaming agents, so the use of isobutane, which has high solubility in polystyrene resin and excellent foaming ability, together with HFO has been considered.

[0039] On the other hand, it is known that the gas permeability coefficient of styrene-(meth)acrylic acid ester copolymer is much smaller than that of polystyrene resin. Therefore, if HFO is used as a physical foaming agent, the main component of the base resin is styrene-(meth)acrylic acid ester copolymer, and the blending rate of polystyrene resin can be reduced, it may be possible to obtain an extruded foam board that maintains low thermal conductivity for a long period of time. However, the foamability of styrene-(meth)acrylic acid ester copolymer is inferior to that of polystyrene resin. Therefore, research has been conducted mainly on those with a low content of (meth)acrylic acid ester components derived from styrene-(meth)acrylic acid ester copolymer in the base resin.

[0040] Furthermore, in the past, when polystyrene resin was used as the base resin and HFO was used as the physical foaming agent, the foaming property of the polystyrene resin was reduced, and it was not easy to obtain a good extruded foam board. For this reason, in the past, isobutane, which has excellent foaming property for polystyrene resin, was used together with HFO. As a result, since isobutane has a higher thermal conductivity than HFO, the thermal conductivity increases as the compounding rate of isobutane increases, and there was room for further improvement in the problem of obtaining an extruded foam board with low thermal conductivity for a long period of time.

[0041] This effect of maintaining low thermal conductivity may be improved by using a styrene-(meth)acrylic acid ester copolymer instead of polystyrene resin. This is because the gas permeability of HFO, especially HFO-1234ze, to styrene-(meth)acrylic acid ester copolymer is very small, and HFO can be maintained for a long period of time and low thermal conductivity can be maintained. However, resins mainly composed of styrene-(meth)acrylic acid ester copolymer have a problem of poor foamability. Therefore, in the past, in the case of a base resin mainly composed of styrene-(meth)acrylic acid ester copolymer, it was thought that the foamability would decrease because the content of the styrene component, which has excellent foamability, would decrease if the ratio of the (meth)acrylic acid ester component in the base resin increased.

[0042] The present inventors have attempted extrusion foaming using the HFO with a base resin mainly composed of a styrene-(meth)acrylic acid ester copolymer, and have unexpectedly found that a higher content of the (meth)acrylic acid ester component provides better moldability and allows the production of a good extruded foam board, thus completing the present invention. If the content of the (meth)acrylic acid ester component derived from the styrene-(meth)acrylic acid ester copolymer in the base resin is too low, the HFO tends to separate from the foam board, leading to frequent gas spots and a poor appearance of the surface of the extruded foam board. If the content is too high, moldability tends to decrease, making it impossible to produce an extruded foam board.

[0043] When HFO is used as a physical foaming agent, the reason why base resins with a high ratio of (meth)acrylic acid ester components have excellent foaming properties is thought to be that the effect of HFO plasticizing the (meth)acrylic acid ester components in the base resin is greater than the effect of HFO plasticizing polystyrene resin.

[0044] As the flame retardant, a bromine-based flame retardant can be suitably used. Examples of the bromine-based flame retardant include tetrabromobisphenol A, tetrabromobisphenol-A-bis(2,3-dibromopropyl ether), tetrabromobisphenol-A-bis(2-bromoethyl ether), tetrabromobisphenol-A-bis(allyl ether), tetrabromobisphenol-A-bis(2,3-dibromo-2-methylpropyl ether), tetrabromobisphenol S, tetrabromobisphenol-S-bis(2,3-dibromopropyl ether), hexabromocyclododecane, tetrabromocyclooctane, tris(2,3-dibromopropyl)isocyanurate, tribromophenol, decabromodiphenyl oxide, tris(tribromoneopentyl)phosphate, brominated polystyrene, and brominated styrene-butadiene copolymer. These compounds can be used alone or in combination of two or more. Among these brominated flame retardants, from the viewpoint of high thermal stability and high flame retardancy, it is particularly preferable to use brominated compounds of tetrabromobisphenol-A-bis(2,3-dibromopropyl ether), tetrabromobisphenol-A-bis(2,3-dibromo-2-methylpropyl ether), tris(2,3-dibromopropyl)isocyanurate, and styrene-butadiene copolymers. These compounds can be used alone or in combination of two or more kinds.

[0045] The amount of the flame retardant to be blended is preferably 1 part by mass, more preferably 3 parts by mass, per 100 parts by mass of the base resin in order to satisfy a high level of flame retardancy such as the flammability standard for extruded polystyrene foam insulation described in "Test Method A" in the flammability test method of JIS A9521: 2017. In addition, in order to minimize the deterioration of foamability during extrusion and the deterioration of the mechanical properties of the thermoplastic resin foam board, the upper limit of the amount of the flame retardant to be blended is preferably 10 parts by mass, more preferably 7 parts by mass, per 100 parts by mass of the base resin.

[0046] Furthermore, in the present invention, a flame retardant auxiliary can be blended in combination with the flame retardant for the purpose of further improving the flame retardancy of the extruded foam board. Examples of the flame retardant auxiliary include diphenylalkanes and diphenylalkenes such as 2,3-dimethyl-2,3-diphenylbutane, 2,3-diethyl-2,3-diphenylbutane, 3,4-dimethyl-3,4-diphenylhexane, 3,4-diethyl-3,4-diphenylhexane, 2,4-diphenyl-4-methyl-1-pentene, and 2,4-diphenyl-4-ethyl-1-pentene, triphenylphosphate, cresyl di-2,6-xylenyl phosphate, antimony trioxide, diantimony pentoxide, ammonium sulfate, zinc stannate, cyanuric acid, isocyanuric acid, triallyl isocyanurate, melamine cyanurate, melamine, melam, and melem, and other nitrogen-containing cyclic compounds, silicone compounds, inorganic compounds such as boron oxide, zinc borate, and zinc sulfide, and phosphorus compounds such as red phosphorus, ammonium polyphosphate, and phosphazene. These compounds can be used alone or in combination of two or more.

[0047] The method of blending the flame retardant into the thermoplastic resin includes a method of feeding a predetermined ratio of the flame retardant together with the thermoplastic resin to a raw material feed section provided upstream of the extruder and kneading the flame retardant together with the thermoplastic resin in the extruder. In addition, the flame retardant can be fed into the thermoplastic resin melt from a flame retardant feed section provided in the extruder. When feeding the flame retardant into the extruder, a method of feeding a dry blend of the flame retardant and the thermoplastic resin into the extruder, a method of feeding a liquid flame retardant that has been heated and melted in advance into the extruder, or a method of preparing a master batch containing the flame retardant and the thermoplastic resin as the base resin and feeding the master batch into the extruder can be adopted. In particular, in order to improve dispersibility, it is preferable to adopt a method of preparing a master batch containing the flame retardant and feeding the master batch into the extruder. The blending method of the flame retardant assistant is the same as the method of feeding the flame retardant.

[0048] In the method of the present invention, a radiation suppressor can be blended with the base resin to further improve the heat insulation. Examples of the radiation suppressor include metal oxides such as titanium oxide, metals such as aluminum, ceramics, fine powders such as carbon black and graphite, infrared shielding pigments, and hydrotalcite. These can be used alone or in combination. The blending amount of the radiation suppressor is about 0.5 to 10 parts by mass, preferably 1 to 8 parts by mass, based on 100 parts by mass of the base resin. When two or more types of radiation suppressors are used, the blending amount means the total amount.

[0049] In the present invention, various additives such as cell regulators, colorants such as pigments and dyes, heat stabilizers, and fillers may be appropriately blended with the base resin, if necessary.

[0050] As the bubble regulator, for example, inorganic powders such as talc, kaolin, mica, silica, calcium carbonate, barium sulfate, aluminum oxide, clay, bentonite, diatomaceous earth, and conventionally known chemical foaming agents such as azodicarbodiamide can be used. Among them, talc is preferred because it does not inhibit flame retardancy and is easy to adjust the bubble size. In particular, it is preferred to use talc having a particle size of 0.1 to 20 μm, more preferably 0.5 to 15 μm, as specified in JIS Z8901:2006. The amount of the bubble regulator to be added varies depending on the type of the bubble regulator, the target bubble size, and the like, but is generally 0.01 to 8 parts by mass, more preferably 0.01 to 5 parts by mass, and particularly preferably 0.05 to 3 parts by mass, relative to 100 parts by mass of the base resin.

[0051] The apparent density of the extruded foam board is preferably 20 kg / m or less because this improves the manufacturing stability and mechanical strength of the extruded foam board. 3 It is preferable that the thickness is 25 kg / m 3 More preferably, it is 30 kg / m 3 In order to improve the heat insulating property and ensure the light weight, the upper limit of the apparent density is preferably 50 kg / m 3 and preferably 45 kg / m 3 More preferably, it is 40 kg / m 3 It is even more preferable that:

[0052] The thickness of the extruded foam board is appropriately set depending on the purpose of use, and is not particularly limited, but from the viewpoint of use as a heat insulating material, it is preferably 25 mm or more, more preferably 35 mm or more, and even more preferably 45 mm or more. The upper limit of the thickness is about 150 mm.

[0053] The cross-sectional area of ​​the extruded foam board perpendicular to the extrusion direction and parallel to the thickness direction is 100 cm 2 More preferably, it is 300 cm or more. 2 More preferably, 400 cm 2 That's all.

[0054] Since the method of the present invention has excellent manufacturing stability, the results of a small-sized experimental machine can be easily transferred to a large-sized actual machine. Therefore, the extruded foam plate having a large cross-sectional area can be easily produced. On the other hand, if the manufacturing stability is not sufficient, the results of the small-sized experimental machine cannot be transferred to a large-sized actual machine, and the extruded foam plate having a desired large cross-sectional area cannot be produced.

[0055] The extruded foam board preferably has a closed cell ratio of 85% or more, more preferably 90% or more, even more preferably 92% or more, and particularly preferably 95% or more, in order to improve long-term heat insulation.

[0056] The closed cell ratio of the extruded foam board is measured by cutting out cut samples from a total of 5 randomly selected locations of the extruded foam board, determining the closed cell ratio for each measurement sample, and adopting the arithmetic average value of the closed cell ratio at the 5 locations. The cut sample is a sample without a skin cut into a size of 45 mm length x 20 mm width x 25 mm thickness from the extruded foam board. If the thickness is too thin to cut out a sample of 25 mm in the thickness direction, for example, two samples (cut samples) cut into a size of 45 mm length x 20 mm width x 12.5 mm thickness are stacked and measured. The closed cell ratio S (%) is calculated by the following formula (3) using the true volume Vx of the thermoplastic resin foam measured using an air comparison type specific gravity meter (for example, Toshiba Beckman Co., Ltd., air comparison type specific gravity meter, model: 930) according to procedure C of ASTM-D2856-70.

[0057] S(%)=(Vx-W / ρ)×100 / (VA-W / ρ)···(3) Vx: The true volume (cm) of the cut sample determined by measurement using an air-comparison type hydrometer 3 ) (This corresponds to the sum of the volume of the resin constituting the cut sample of the foam and the total volume of the air bubbles in the closed cell portion of the cut sample.) VA: Apparent volume (cm) of the cut sample calculated from the outer dimensions of the cut sample used in the measurement 3 ) W: Total weight of cut sample used for measurement (g) ρ: Density of the base resin constituting the thermoplastic resin foam (g / cm 3 )

[0058] The thermal conductivity of the extruded foam board of the present invention one day after production is preferably 0.024 W / (m K) or less, more preferably 0.023 W / (m K) or less, even more preferably 0.022 W / (m K) or less, and particularly preferably 0.021 W / (m K) or less.

[0059] Furthermore, the extruded foam of the present invention preferably has a thermal conductivity of 0.027 W / (m K) or less 1500 days after production, more preferably 0.026 W / (m K) or less, and even more preferably 0.025 W / (m K) or less. In order for the extruded foam board to exhibit stable long-term thermal insulation properties, it is preferable that the difference between the thermal conductivity 1500 days after production and the thermal conductivity 1 day after production is as small as possible.

[0060] The thermal conductivity is measured by cutting a test piece (length 200 mm × width 200 mm × thickness) without any skin from an extruded foam board immediately after production and storing the test piece in an atmosphere of 23°C and 50% humidity according to the flat plate heat flow meter method (two heat flow meter method, high temperature side 38°C, low temperature side 8°C, average temperature 23°C) described in JIS A1412-2:1999.

[0061] The thermal conductivity 1500 days after production is measured using samples that have been subjected to an accelerated test in accordance with JIS A1486: 2014. According to this method, for example, the thermal conductivity measured 60 days after production using a sample obtained by slicing a 50 mm thick extruded foam board to a thickness of 10 mm corresponds to the thermal conductivity of the extruded foam board approximately 1500 days after production. EXAMPLES

[0062] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples in any way.

[0063] In the examples and comparative examples, extruded foam boards were produced using the following equipment and raw materials.

[0064] [Extrusion equipment] A manufacturing device was used in which a first extruder with an inner diameter of 180 mm and a second extruder with an inner diameter of 225 mm were connected in series, a physical foaming agent injection port was provided near the end of the first extruder, and a flat die equipped with a resin discharge port (die lip) with a rectangular cross section with a gap of 2.5 mm and a width of 400 mm was connected to the outlet of the second extruder. A shaping device (guider) consisting of a pair of upper and lower polytetrafluoroethylene resin plates was attached to the resin outlet of the flat die so that the upper and lower resin plates were parallel to each other.

[0065] (thermoplastic resin) Styrene-(meth)acrylic acid ester copolymer (1) Abbreviation "MS1": Styrene-methyl methacrylate copolymer: "MS750" manufactured by Toyo Styrene Co., Ltd. (M component-75% by mass, styrene component-25% by mass, melt viscosity (200°C, 100 sec -1 )2440 Pa·s,) (2) Abbreviation "MS2": Styrene-methyl methacrylate copolymer: "MS200" manufactured by Toyo Styrene Co., Ltd. (M component-20% by mass, styrene component-80% by mass, melt viscosity (200°C, 100 sec -1 )1980Pa·s) (3) Abbreviation "MS3": styrene-methyl methacrylate copolymer: recycled raw material of Example 1 (M component-75% by mass / styrene component-25% by mass, melt viscosity (200°C, 100 sec -1 )2190 Pa·s) (4) Abbreviation "PMMA": Polymethyl methacrylate resin: "TF9" manufactured by Mitsubishi Chemical Corporation (M component-100% by mass, styrene component-0% by mass, melt viscosity (200°C, 100 sec -1 )3290Pa·s)

[0066] The M component refers to a methacrylic acid ester component derived from a styrene-methacrylic acid ester copolymer. MS3 was prepared by crushing the extruded foam board obtained in Example 1 in a crusher, feeding it to a single-screw extruder with an inner diameter of 90 mm and L / D=50 and kneading it at a maximum temperature of 220°C. The molten resin was extruded at a discharge rate of 250 kg / hour and pelletized to obtain pelletized styrene-methyl methacrylate copolymer (MS3).

[0067] The type, manufacturer, product name, and melt viscosity of each of the above resins are summarized in Table 1.

[0068] [Table 1]

[0069] The melt viscosity of the thermoplastic resin was measured by the following method using a Capillograph 1D manufactured by Toyo Seiki Seisakusho Co., Ltd. A capillary with a hole diameter of 1.0 mm and a length of 10.0 mm was attached to the tip of a cylinder with a diameter of 9.55 mm and a length of 350 mm. After heating the cylinder and the capillary to 200°C, the cylinder was filled with a measurement sample (resin pellets), which was sufficiently melted by preheating for 4 minutes and then heated at a shear rate of 100 sec. -1 The melt viscosity of the resin was measured under the above conditions.

[0070] (Physical foaming agent) (1) Hydrofluoroolefin (HFO): 1,3,3,3-tetrafluoropropene (HFO-1234ze) (2) Hydrofluoroolefin (HFO): 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) (3) Isobutane (iB) (4) Ethanol (EtOH) (5)Water

[0071] (Flame retardant) As a flame retardant, a bromide butadiene-styrene block copolymer, "Emerald Innovation 3000" manufactured by LANXESS KK, was used.

[0072] (Foam regulator) Talc "Hi-Filler #12" manufactured by Matsumura Sangyo Co., Ltd. was used as the bubble adjusting agent.

[0073] (Radiation suppressant) (1) Graphite: "CP-N" (flake graphite) manufactured by Nippon Graphite Industry Co., Ltd., primary particle size (d50) = 10 μm (2) Titanium oxide: "JR-405" manufactured by Teika Co., Ltd., primary particle size (d50) = 0.2 μm

[0074] Examples 1 to 11, Comparative Examples 1 to 5 The types and blending ratios of thermoplastic resins, flame retardants, talc, and radiation suppressants shown in Tables 2 and 3 (where the total blending amount of each resin is 100% by mass) were fed to the first extruder and heated and kneaded to form a molten resin composition, to which a physical foaming agent was fed from the physical foaming agent inlet, and the molten resin composition further melt-kneaded in the first extruder was transferred to the subsequent second extruder to adjust the resin temperature to a foaming-suitable temperature of 119°C, and then extruded from the die lip into a guider at a discharge rate of 700 kg / h and a die pressure of 6 to 8 MPa, and molded (shaped) into a plate by passing through the guider while foaming to obtain a base plate with a thickness of 55 mm. Then, the surface skins on both sides of the base plate were evenly scraped to obtain a plate-shaped extruded foam plate (width 910 mm x length 2000 mm x thickness 50 mm).

[0075] [Table 2]

[0076] [Table 3]

[0077] The physical properties of the extruded foam boards produced were measured and evaluated, and the results are shown in Tables 4 and 5.

[0078] [Table 4]

[0079] [Table 5]

[0080] In Tables 4 and 5, the apparent density, closed cell ratio, cell diameter, and thermal conductivity were measured by the following methods, and further the moldability and manufacturing stability were evaluated according to the following criteria.

[0081] <Apparent density> The apparent density was measured in accordance with JIS K6767 (1999). Rectangular samples measuring 50 mm long x 50 mm wide x 50 mm thick were cut from three locations, namely the widthwise center and both widthwise ends, of each extruded foam board, and the apparent density of each sample was measured. The arithmetic mean of the measurements at the three locations was used as the apparent density.

[0082] <Closed bubble rate> The cut samples were cut from three locations, the center and both ends of the width direction of the extruded foam plate, to prepare measurement samples, and the closed cell ratio of each measurement sample was measured. The arithmetic mean value of the closed cell ratios at the three locations was used as the closed cell ratio. The cut samples were cut from the extruded foam plate to a size of 25 mm length x 25 mm width x 25 mm thickness. The closed cell ratio of the sample was measured using an air comparison type specific gravity meter (Model: 930, manufactured by Toshiba Beckman Co., Ltd.) according to Procedure C of ASTM-D2856-70, and calculated from the above formula (3). The arithmetic average value of three points was taken as the closed cell ratio.

[0083] <Bubble diameter> The bubble diameter was measured at the center (the part 5 mm above and below the center in the width direction from the line that bisects the foam board in the thickness direction, with the center at the line) of a perpendicular cross section of the foam board in the extrusion direction (a perpendicular cross section bisected at the center in the width direction, parallel to the extrusion direction of the extruded foam) by adjusting the magnification from 50 to 200 times to obtain an enlarged photograph so that the number of cells in the photograph was approximately 200 to 500. The bubble diameter of each bubble in the thickness direction was measured using the image processing software NS2K-pro manufactured by Nano System Co., Ltd., and the arithmetic average value was used as the bubble diameter.

[0084] <Thermal conductivity> Test pieces without the skin, measuring 200 mm in length, 200 mm in width, and 50 mm in thickness, were cut out from the extruded foam board immediately after production, and stored for one day in an atmosphere at a temperature of 23°C and a humidity of 50%, and the thermal conductivity of the test pieces was measured based on JIS A1412-2 (1999) flat plate heat flow meter method (two heat flow meter method, high temperature side 38°C, low temperature side 8°C, average temperature 23°C).

[0085] The thermal conductivity after 1500 days of manufacture was measured on a test piece subjected to test method A of the long-term accelerated change test of thermal resistance in accordance with JIS A1486 (2014). Specifically, a test piece without a molded skin measuring 200 mm x 200 mm x 10 mm was cut evenly from both sides of the center of a 50 mm-thick extruded foam board immediately after manufacture, and stored in a constant temperature and humidity room at a temperature of 23°C and a relative humidity of 50%. The thermal conductivity of the test piece after 60 days of manufacture (corresponding to 1500 days after the manufacture of a 50 mm-thick extruded foam board) was measured based on the flat plate heat flow meter method (two heat flow meter method, high temperature side 38°C, low temperature side 8°C, average temperature 23°C) described in JIS A1412-2 (1999).

[0086] <Moldability> The moldability was evaluated according to the following criteria. ⊚: The foaming state was good, and the surface was free of roughness or gas spots, and a plate-shaped base plate with an extremely good appearance was stably obtained. ◯: The foaming state was relatively good. Although surface roughness and gas spots rarely occurred, a generally good plate-shaped base plate was obtained. ×: Roughness or numerous gas spots were observed on the surface of the foam board, and a good-quality base board and extruded foam board were not obtained.

[0087] <Manufacturing stability> The evaluation of the production stability was performed according to the following criteria. ◯: When the molten resin composition was foamed and molded into a plate using a molding tool, a base plate could be produced stably without any problems. ×: When the molten resin composition was foamed and molded into a plate using a molding tool, the original plate was frequently broken.

[0088] Example 1 is an example in which a styrene-methyl (meth)acrylate copolymer with a (meth)acrylic acid ester content of 75% by mass was used as the base resin, and HFO-1234ze was used as the physical foaming agent. The extruded foam plate had excellent moldability and production stability, and the extruded foam plate had low long-term thermal conductivity. Example 2 is an example in which an extruded foam board was produced in the same manner as in Example 1, except that a styrene-methyl (meth)acrylate copolymer with a (meth)acrylic acid ester content of 62.5 mass% was used as the base resin and HFO-1234ze was used as the physical foaming agent. The moldability and production stability of the extruded foam board produced were excellent, and the extruded foam board obtained had low long-term thermal conductivity. Example 3 is an example in which an extruded foam board was produced in the same manner as in Example 1, except that a styrene-methyl (meth)acrylate copolymer with a (meth)acrylic acid ester content of 62.5 mass% was used as the base resin, and a mixed foaming agent of HFO-1234ze (0.7 mol%) and HFO-1233zd (0.3 mol%) was used as the physical foaming agent. The moldability and production stability of the extruded foam board production were excellent, and the obtained extruded foam board had low long-term thermal conductivity. Example 4 is an example in which an extruded foam board was produced in the same manner as in Example 3, except that a styrene-methyl (meth)acrylate copolymer containing 50 mass% of a (meth)acrylic acid ester component was used as the base resin, and a mixed foaming agent of HFO-1234ze (0.8 mol%) and HFO-1233zd (0.2 mol%) was used as the physical foaming agent. The moldability and production stability of the extruded foam board produced were excellent, and the extruded foam board obtained had low long-term thermal conductivity. Example 5 is an example in which an extruded foam board was produced in the same manner as in Example 3, except that a styrene-methyl (meth)acrylate copolymer containing 50% by mass of a (meth)acrylic acid ester component was used as the base resin. The moldability and production stability of the extruded foam board were excellent, and the extruded foam board obtained had low long-term thermal conductivity. Example 6 is an example in which an extruded foam board was produced in the same manner as in Example 1, except that a mixed blowing agent of HFO-1234ze (0.4 mol%) and HFO-1233zd (0.6 mol%) was used as the physical blowing agent. The moldability and production stability of the extruded foam board were excellent, and the extruded foam board obtained had low long-term thermal conductivity. Example 7 is an example in which an extruded foam board was produced in the same manner as in Example 1, except that a mixed blowing agent of HFO-1234ze (0.5 mol%) and isobutane (0.5 mol%) was used as the physical blowing agent. The moldability and production stability of the extruded foam board produced were excellent, and the extruded foam board obtained had low long-term thermal conductivity. Example 8 is an example in which an extruded foam board was produced in the same manner as in Example 1, except that the amount of talc added was reduced and a radiation inhibitor (graphite / titanium oxide) was added. The extruded foam board produced had excellent moldability and production stability, and the extruded foam board produced had low long-term thermal conductivity. Example 9 is an example in which an extruded foam board was produced in the same manner as in Example 1, except that a mixed resin containing the recycled resin from the extruded foam board obtained in Example 1 was used as the base resin. The extruded foam board produced had excellent moldability and production stability, and the extruded foam board produced had low long-term thermal conductivity. Example 10 is an example in which an extruded foam board was produced in the same manner as in Example 7, except that a styrene-methyl (meth)acrylate copolymer with a (meth)acrylic acid ester content of 32.9 mass% was used as the base resin. The moldability and production stability of the extruded foam board were excellent, and the extruded foam board obtained had low long-term thermal conductivity. Example 11 is an example in which an extruded foam board was produced in the same manner as in Example 7, except that a styrene-methyl (meth)acrylate copolymer with a (meth)acrylic acid ester content of 27.6 mass% was used as the base resin. The moldability and production stability of the extruded foam board were excellent, and the extruded foam board obtained had low long-term thermal conductivity.

[0089] Comparative Example 1 is an example in which an extruded foam board was produced in the same manner as in Example 1, except that a styrene-methyl (meth)acrylate copolymer with a (meth)acrylic acid ester content of 20 mass% was used, and a mixed blowing agent of HFO-1234ze (0.8 mol%) and HFO-1233zd (0.2 mol%) was used as the physical blowing agent. Because the (meth)acrylic acid ester content of the base resin was low, gas spots occurred frequently, and the resulting extruded foam board had poor moldability. In Comparative Example 2, an extruded foam board was produced in the same manner as in Example 1, except that a styrene-methyl (meth)acrylate copolymer with a (meth)acrylic acid ester content of 20% by mass was used. Gas spots occurred more frequently than in Comparative Example 1, and an extruded foam board could not be obtained. In Comparative Example 3, an extruded foam board was produced in the same manner as in Example 3, except that polymethyl methacrylate resin (PMMA) was used as the base resin. Shrinkage immediately after production was large, and an extruded foam board could not be obtained. In Comparative Example 4, an extruded foam board was produced in the same manner as in Example 1, except that polymethyl methacrylate resin (PMMA) was used as the base resin. Shrinkage immediately after production was large, and an extruded foam board could not be obtained. Comparative Example 5 is an example in which a styrene-methyl (meth)acrylate copolymer with a (meth)acrylic acid ester content of 62.5 mass% was used as the base resin, and a mixed blowing agent of HFO-1234ze (0.2 mol%) and isobutane (0.8 mol%) was used as the physical blowing agent. The production stability was poor, and breakage frequently occurred in the forming device (guider).

Claims

1. A method for producing an extruded thermoplastic resin foam plate, comprising the steps of extruding and foaming a foamable resin composition obtained by kneading a base resin, a physical foaming agent, and a flame retardant, and molding the composition into a plate shape using a molding tool, the base resin contains a styrene-(meth)acrylic acid ester copolymer as a main component, the content of the (meth)acrylic acid ester component derived from the styrene-(meth)acrylic acid ester copolymer in the base resin is 25% by mass or more and 90% by mass or less, the total amount of the physical foaming agent is 0.8 mol or more and 1.3 mol or less per 1 kg of the base resin, and the physical foaming agent contains a hydrofluoroolefin, and the total amount of the hydrofluoroolefin is 0.5 mol or more and 1.3 mol or less per 1 kg of the base resin.

2. The method for producing an extruded thermoplastic resin foam board according to claim 1, wherein the content of the (meth)acrylic acid ester component derived from the styrene-(meth)acrylic acid ester copolymer in the base resin is 50% by mass or more and 80% by mass or less.

3. 3. The method for producing a thermoplastic resin foam board according to claim 1, wherein the styrene-(meth)acrylic acid ester copolymer is a styrene-methyl methacrylate copolymer.

4. The method for producing a thermoplastic resin foam board according to any one of claims 1 to 3, characterized in that a total amount of the hydrofluoroolefins is 0.5 mol or more and 1.0 mol or less per 1 kg of the base resin.

5. the hydrofluoroolefin comprises 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) and / or 1,3,3,3-tetrafluoropropene (HFO-1234ze); The method for producing a thermoplastic resin foam board according to any one of claims 1 to 4, characterized in that the total amount of 1-chloro-3,3,3-trifluoropropene (HFO-1233zd) and / or 1,3,3,3-tetrafluoropropene (HFO-1234ze) is 0.5 mol or more per kg of the base resin.

6. The method for producing a thermoplastic resin foam board according to any one of claims 1 to 4, characterized in that the hydrofluoroolefin contains 1,3,3,3-tetrafluoropropene (HFO-1234ze), and the amount of 1,3,3,3-tetrafluoropropene (HFO-1234ze) is 0.5 mol or more per kg of the base resin.

7. The method for producing a thermoplastic resin foam board according to claim 6, characterized in that the content (X) [mass%] of the (meth)acrylic acid ester component derived from the styrene-(meth)acrylic acid ester copolymer in the base resin and the blending amount (Y) [mol / kg of base resin] of 1,3,3,3-tetrafluoropropene (HFO-1234ze) satisfy the following formula (1): Y < 0.024X-0.4...(1)

Citation Information

Patent Citations

  • Resin foam

    JP1983125724A

  • Foamed styrene copolymer resin sheet and its formed material

    JP2000273230A

  • Method for producing styrenic resin foam

    JP2008133424A

  • Styrene resin-extruded / foamed plate

    JP2009215504A

  • Thermoplastic resin foam body

    JP2019189666A